2018
DOI: 10.1039/c8sc00555a
|View full text |Cite
|
Sign up to set email alerts
|

Highly active nano-sized iridium catalysts: synthesis and operando spectroscopy in a proton exchange membrane electrolyzer

Abstract: Ultra-high purity nano-sized iridium enclosed in a monolayer of IrIII/IrIV oxides/hydroxides leads to an enhancement in OER activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 47 publications
9
90
2
Order By: Relevance
“…Note however that, based on the linear dependence of these peak potentials with pH, Kuo et al 39 suggested that these peaks may be ascribed to the transition between surface adsorbed hydroxyl and oxygen. The absence of electrical charge associated with the underpotential deposition of H was another evidence that a stable oxide layer had formed after the electrochemical conditioning stage 30,40 For all materials, we measured OER mass activities approaching 250 A g Ir -1 at 1.51 V vs. RHE (η = 280 mV), and exceeding those of the commercial IrO catalyst (at least times), and those of IrO 2 particles supported onto ATO reported by Lettenmeier et al 41 ,…”
Section: Catalystsmentioning
confidence: 55%
“…Note however that, based on the linear dependence of these peak potentials with pH, Kuo et al 39 suggested that these peaks may be ascribed to the transition between surface adsorbed hydroxyl and oxygen. The absence of electrical charge associated with the underpotential deposition of H was another evidence that a stable oxide layer had formed after the electrochemical conditioning stage 30,40 For all materials, we measured OER mass activities approaching 250 A g Ir -1 at 1.51 V vs. RHE (η = 280 mV), and exceeding those of the commercial IrO catalyst (at least times), and those of IrO 2 particles supported onto ATO reported by Lettenmeier et al 41 ,…”
Section: Catalystsmentioning
confidence: 55%
“…While partly due to iridium's rarity, this difference is also a testament to the exceptionally good HER activity of platinum and the limitations that the scaling relations, discussed below, impose on current OER catalysts, including iridium. A comparison between HER activity of platinum and the OER activity for a state-of-the-art iridium-based catalyst 12 ( Figure 1A) underscores this, demonstrating 3-4 orders of magnitude difference.…”
Section: Impact Of Metal Scarcity On Scale-upmentioning
confidence: 81%
“…The contribution of the IrCl3 being small, its observation in the powder diffraction patterns can be attributed to the large size of IrCl3 crystals (see Ref. 9 ). IrO2 sample is fully represented by the rutile phase oxide.…”
Section: X-ray Powder Diffraction (Xrd)mentioning
confidence: 99%
“…Fitting of the spectra was performed using five doublets with Ir4f7/2 peak positions at 60.85 eV, 61.70 eV, 63.00 eV, 62.40 eV and 64.20 eV, and attributed to metallic Ir; Ir (IV) and its satellite; Ir (III) and its satellite, correspondingly as it was discussed in our previous publications 2,9 . Ir4f XP spectra recorded on Ir@IrOx anode under different polarizations and 2 photon energies are displayed in Figure S 11 and Figure S 12.…”
Section: Ir4f Xp Spectra: Evolution Under Potential Quantitative Anamentioning
confidence: 99%